EPCO-27. REVEALING TUMOR HETEROGENEITY AND IMMUNE MICROENVIRONMENT IN NF-1 GLIOMA BY SINGLE-CELL GENE EXPRESSION PROFILING. (14th November 2022) - D'Angelo, Fulvio; Garofano, Luciano; Oh, Young Taek; Najac, Ryan; Ceccarelli, Michele; Eoli, Marica; Sanson, Marc; Lasorella, Anna; Iavarone, Antonio
Abstract: Germline mutations in the NF1 tumor suppressor gene cause neurofibromatosis type 1 (NF-1), the most common human genetic cancer predisposition syndrome. NF1 patients are prone to develop peripheral and central nervous system tumors, with glioma occurring in 15-20% of patients. The molecular profiles of glioma from patients with NF-1 have been previously explored by large scale DNA and RNA bulk analyses, providing the first comprehensive genetic landscape of NF-1 glioma. However, the intra-tumoral architecture and the microenvironment organization remained largely concealed within the global bulk profile. Here, to characterize the complexity of molecular states of both malignant and non-malignant cells, we profiled NF-1 glioma gene expression at individual cell resolution. We performed single-nuclei RNA sequencing (Nucseq) on frozen NF-1 glioma specimens, including high-grade and low-grade tumors. The functional classification of the transcriptional programs activated in the individual tumor cells identified three main molecular states that partially overlapped with the cellular subtypes of sporadic glioblastoma. Tumor cells of low-grade NF-1 glioma exhibited marked enrichment of neuronal functions, suggesting that the gliomagenesis process in the context of NF1 inactivation might be supported by specialized neuronal activities. Conversely, the proliferative state characterized high-grade NF-1 glioma, indicating that cell cycle-associated pathways are drivers of tumor progression. The single-cell deconvolution of immune microenvironment in NF-1 low grade glioma revealed infiltration of CD8 + T lymphocytes and the active crosstalk of these cells with pro-inflammatory macrophages and mature dendritic cells, supporting a possible anti-tumor cell-mediated response. The identification of divergent tumor cell states as well as the characterization of the immune infiltrates provide new insights for accurate stratification of NF-1 glioma patients and to inform personalized therapeutics.